2011
DOI: 10.1371/journal.pone.0016795
|View full text |Cite
|
Sign up to set email alerts
|

Role of HDAC3 on p53 Expression and Apoptosis in T Cells of Patients with Multiple Sclerosis

Abstract: BackgroundHistone deacetylase 3 (HDAC3) belongs to a family of proteins which plays an important role in protein acetylation, chromatin remodeling and transcription of genes, including those that are involved in cell proliferation and cell death. While increased expression of HDAC3 is seen in neoplastic cells, the role of HDAC3 in T cells and their role in autoimmune disease is not known.Methodology/Principal FindingsApplying Affymetrix GeneChip Human Gene 1.0 ST Array and the mixed effects model for gene set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…68 HDACi ranging from pan-HDACi, such as TsA, 69,70 SAHA, 71 butyrate, 72 scriptaid, 70 trapoxin, 69 to class I-specific HDACi, such as MS-275, 73 and class II-specific HDACi, such as MC1575, 74 were all shown to up-regulate p21 in tumor cells, but less is known of their effects in normal lymphocytes. Human PBMCs incubated for 2 days with a high proapoptotic concentration of TsA showed a moderate increase in p21 mRNA expression, 75 but there were no data reported regarding the cell subsets involved. The finding that butyrate blocked the proliferation in primary cultures of both WT and p21-deficient cells 76 raises doubts as to the role of p21 in inhibition of T-cell divisions by HDACi.…”
Section: Stage 2: Division Of Activated Naive T Cellsmentioning
confidence: 99%
“…68 HDACi ranging from pan-HDACi, such as TsA, 69,70 SAHA, 71 butyrate, 72 scriptaid, 70 trapoxin, 69 to class I-specific HDACi, such as MS-275, 73 and class II-specific HDACi, such as MC1575, 74 were all shown to up-regulate p21 in tumor cells, but less is known of their effects in normal lymphocytes. Human PBMCs incubated for 2 days with a high proapoptotic concentration of TsA showed a moderate increase in p21 mRNA expression, 75 but there were no data reported regarding the cell subsets involved. The finding that butyrate blocked the proliferation in primary cultures of both WT and p21-deficient cells 76 raises doubts as to the role of p21 in inhibition of T-cell divisions by HDACi.…”
Section: Stage 2: Division Of Activated Naive T Cellsmentioning
confidence: 99%
“…The epigenetic influence of HDIs on gene expression make them a useful new class of pharmacological agents that could ameliorate various disease conditions. For example, HDIs also promote neuronal survival in ischemic injury, [14][15][16][17] multiple sclerosis [18,19], and Alzheimer's and Huntington's disease models [20][21][22][23][24]. These multiple roles of HDIs can be attributed to alterations in the expression of different gene sets by increasing acetylation of chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, accumulative evidence has suggested that inhibition of HDACs leads to the expression of tumor suppressor genes, such as p21 (7,8), p27 (8,9), and p53 (7,10), therefore inducing cell cycle arrest and cell apoptosis (1,9). HDAC inhibitors are emerging as a new class of anticancer agents for the treatment of solid and hematological malignancies (6).…”
mentioning
confidence: 99%